Predictive models for tuberculous pleural effusions in a high tuberculosis prevalence region - Demirer, Ersin; Miller, Andrew Cate; Kunter, Erdoğan; Kartalo?lu, Zafer; Barnett, Scott D.; Elamin, Elamin M. (Springer, 2012)
Patients with pleural effusions who reside in geographic areas with a high prevalence of tuberculosis frequently have similar clinical manifestations of other diseases. The aim of our study was to develop a simple but accurate clinical score for differential diagnosis of tuberculosis pleural effusion (TPE) from non-TB pleural effusion (NTPE). This was an unblinded, prospective study of Turkish patients 18 years of age or older with pleural effusion of indeterminate etiology conducted from June 2003 to June 2005. Unconditional logistic regression models were used to discriminate TPE cases from NTPE cases. Standard errors for the area under the curve (AUC) were calculated using the Mann-Whitney method. Data were statistically significance if two-tailed P < 0.05. A total of 63.3% (157/248) of the patients had TPE while 36.7% (91/248) of the patients had other etiologies for pleural effusions. We were able to provide a predictive model of TPE that included age < 47 years and either pleural fluid adenosine deaminase enzyme (PADA) > 35 U/l or pleural serum protein ratio > 0.710. However, only the combination of age < 47 and PADA > 35 U/l was significant (odds ratio [OR]: 7.46; 95% confidence interval [CI]: 3.99-13.96). The generated summary score (range = 0-6) was significantly predictive of TPE (OR: 2.91; 95% CI: 2.18-3.89) and with high AUC (0.79). We propose an affordable model that includes age < 47 years and PADA > 35 U/l for timely diagnosis of TPE in geographical regions with a high prevalence of TB.
WOS: 000302146900015
PubMed ID: 22057296
Keywords: Adenosine Deaminase Enzyme; Lactate Dehydrogenase Enzyme; Pulmonary Tuberculosis; Tuberculous Pleural Effusion